Retained plastic instrument after 5 years of illegal abortion: a case report and literature review - Romuald, Randriamahavonjy; A. Ratsiatosika, Tanjona; Sonia, Rasolofomanana; Andriniaina, Ravelojaona; Mahefa, Rakotonirina; A. Lantonirina, Rainibarijaona; Ando-Miora, Rakotonirina; H. Rakotovao, Andrianampanalinarivo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The retained of a foreign body during a surgical procedure is defined by the forgetting of a material, left by inattention in the body of the patient during this act. It is a rare event but is responsible for high morbidity and mortality. Authors report a retained foreign body incidentally discovered during a caesarean section. The patient had performed an illegal abortion by endo-uterine instrument which was complicated by uterine perforation five years previously. She was pregnant at 37 weeks and presented to the emergency department for bleeding and diagnosed as placenta previa. The antecedent of abortion had not been informed because it is an illegal act in Madagascar. The plastic instrument was in the broad ligament in contact with the ureter and the uterine artery. Caesarean section, the removal of the catheter and postoperative recovery was uneventful. Foreign body retention remains a malpractice and the diagnosis must be made in the face of chronic pain in patients who have undergone surgery.